EFEK PENGGUNAAN PUPUK ORGANIK DAN INOKULAN MIKROBATERHADAP PERTUMBUHAN JATI SUPER (Tectona grandis L.f.) PADA LAHAN BEKAS TAILING POND PENAMBANGAN EMAS DI CIKOTOK - Supriyati, Dyah; Agustiyani, Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Experiment using organic fertilizer and microbial community to support the growth ofÃ‚Â Tectona grandis L.f in the cyanide contaminated-soil has been conducted in gold tailingÃ‚Â pond Cikotok. Microbes used in this experiment were mixed of cyanide degradingbacteria,Nitrogen fixing-bacteria, and Phosphat solubilizing-bacteria. The results showÃ‚Â that the microbes given in the Tectona grandis L.f plantation was significantly supportingÃ‚Â the growth of the plants and reduced cyanide from the contaminated soil, but did notÃ‚Â influence the microbe population of the soil.Key word: Phytoremediation, Cyanide, Tectona grandis L.f.